Uncovering the effects of gender affirming hormone therapy on skeletal muscle and epigenetics: protocol for a prospective matched cohort study in transgender individuals (the GAME study) - Andrew Palmer; Teddy Cook; Andrew Garnham; Nir Eynon; Ariel Ginger; Sav Zwickl; Patrice R Jones; Sarah Voisin; Brendan J Nolan; Shanie Landen; Macsue Jacques; Beau Newell; et al. (BMJ Open, 2022)
Introduction Gender affirming hormone therapy (GAHT) is increasingly used by transgender individuals and leads to shifts in sex hormone levels. Skeletal muscle is highly responsive to hormone activity, with limited data on the effects of GAHT on different human tissues. Here, we present the protocol for the GAME study (the effects of Gender Affirming hormone therapy on skeletal Muscle training and Epigenetics), which aims to uncover the effects of GAHT on skeletal muscle ‘omic’ profiles (methylomics, transcriptomics, proteomics, metabolomics) and markers of skeletal muscle health and fitness.Methods and analysis This study is a prospective age-matched cohort study in transgender adults commencing GAHT (n=80) and age-matched individuals not commencing GAHT (n=80), conducted at Austin Health and Victoria University in Victoria, Australia. Assessments will take place prior to beginning GAHT and 6 and 12 months into therapies in adults commencing GAHT. Age-matched individuals will be assessed at the same time points. Assessments will be divided over three examination days, involving (1) aerobic fitness tests, (2) muscle strength assessments and (3) collection of blood and muscle samples, as well as body composition measurements. Standardised diets, fitness watches and questionnaires will be used to control for key confounders in analyses. Primary outcomes are changes in aerobic fitness and muscle strength, as well as changes in skeletal muscle DNA methylation and gene expression profiles. Secondary outcomes include changes in skeletal muscle characteristics, proteomics, body composition and blood markers. Linear mixed models will be used to assess changes in outcomes, while accounting for repeated measures within participants and adjusting for known confounders.Ethics and dissemination The Austin Health Human Research Ethics Committee (HREC) and Victoria University HREC granted approval for this study (HREC/77146/Austin-2021). Findings from this project will be published in open-access, peer-reviewed journals and presented to scientific and public audiences.Trial registration number ACTRN12621001415897; Pre-results.